1996
DOI: 10.1046/j.1365-2249.1996.d01-790.x
|View full text |Cite
|
Sign up to set email alerts
|

Morphologically and functionally intact dendritic cells can be derived from the peripheral blood of aged individuals

Abstract: SUMMARYDendritic cells are antigen-presenting cells (APC), which are crucial for the initiation of an immune response. In spite of the well known decline of immune function in old age, no information is yet available on whether dendritic cells are also affected by the ageing process. It was therefore the aim of this study to compare peripheral blood dendritic cells (DC) from old and young healthy individuals. Using granulocyte-macrophage colony-stimulating factor (GM-CSF) and IL-4, DC were propagated from peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
60
0
2

Year Published

1998
1998
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(66 citation statements)
references
References 32 publications
(51 reference statements)
4
60
0
2
Order By: Relevance
“…The MODCs population obtained from aging monocytes displays a typical DC morphology and expresses DC surface markers, such as HLA class II, CD1a, CD11c, CD54, CD80 and CD86, but not CD14. Our observations are in agreement to data of MODCs reported by Lung et al (2000) and Steger et al (1996). Linton et al (2005), using a T cell receptor transgenic mice model, also observed normal immunophenotype of DCs in vivo in aged mice.…”
Section: Numbers Phenotype and Differentiationsupporting
confidence: 93%
See 1 more Smart Citation
“…The MODCs population obtained from aging monocytes displays a typical DC morphology and expresses DC surface markers, such as HLA class II, CD1a, CD11c, CD54, CD80 and CD86, but not CD14. Our observations are in agreement to data of MODCs reported by Lung et al (2000) and Steger et al (1996). Linton et al (2005), using a T cell receptor transgenic mice model, also observed normal immunophenotype of DCs in vivo in aged mice.…”
Section: Numbers Phenotype and Differentiationsupporting
confidence: 93%
“…Szakal et al (2002) reported that in vivo age-related defects in B cell stimulation via the B cell receptor and co-stimulation via CD21/CD21L are related to immune complex-trapping by follicular DCs. Whereas other studies have described no change or even an enhancement (Steger et al, 1996). The conflicting results may be due to different subsets of DCs used (LCs versus myeloid DC versus FDC) and species differences (man versus mouse).…”
Section: Modulation Of Adaptive Immune Responses By Dcsmentioning
confidence: 85%
“…Some of this conflicting data may be attributed to using the SENIEUR protocol for recruitment of subjects. Investigations of monocyte derived DCs (MODCs) have found that DCs subsets are similar in aged and young subjects (Lung et al, 2000;Steger et al, 1996). This variation in opinion regarding changes in numbers of DC subsets with age may reflect differences in experimental protocols and the number of subjects recruited in the different studies (Jing et al, 2009).…”
Section: Numbers Of DC Subsets With Agementioning
confidence: 99%
“…There are reports indicating that DC derived from the peripheral blood of humans do not show significant phenotype or functional alterations with aging (13). On the other hand, DC differentiated in vitro from precursors obtained from the bone marrow of old mice show an increased secretion of IL-10 and a reduced secretion of tumor necrosis factor alpha (TNF-α) and IL-6 after stimulation with lipopolysaccharide compared to the DC obtained from young mice (14).…”
Section: Introductionmentioning
confidence: 99%